THE ERA OF UNMANNED AERIAL VEHICLES IS COMING - Krawczyk Jacek (2021)
The use of UAVs (Unmanned Aerial Vehicles) is constantly increasing due to their technical, operational and economic potential. They are used for recreational and commercial purposes by individuals, companies, organizations and government institutions. Despite the systematic implementation of appropriate safety procedures in air traffic management systems, aviation procedures and safety management systems, it is impossible to completely prevent air accidents. Within 6 months, two air crashes have been reported that involved BEAING 767 Max 8 aircraft. This gives rise to the question whether air accidents involving manned aircraft will become a catalyst for even faster development of UAVs and their greater importance. Purpose: The purpose of the article is to present the potential for the use of UAVs and the measures that should be taken in order to make unmanned aviation competitive against manned aviation. Method: The scientific methods used in the paper include the review and criticism of the literature on the subject, as well as logical analysis and construction. Article type - Review article. Results: The article presents the measures to be implemented in order for unmanned aviation to become competitive against manned aviation and complement other types of transportation services. When introducing new regulations and procedures, the priority should be to ensure the safety of the airspace and other spaces where operations with the use of UAVs will be performed. Conclusions: In order to ensure safety, it is important to equip UAVs with anti-collision devices and airspace detectors informing about any approaching aircraft and obstacles on the actual and potential path, as well as with cameras enabling observation of the airspace around UAVs.